1981
DOI: 10.1115/1.3244449
|View full text |Cite
|
Sign up to set email alerts
|

An Interferometric Study of Combined Free and Forced Convection in a Horizontal Isothermal Tube

Abstract: A Mach-Zehnder interferometer was employed to determine the three-dimensional temperature field, and the circumferential and average Nusselt numbers for laminar flow of air in the entrance region of an isothermal horizontal tube where the velocity and the temperature profiles were developing simultaneously. The influence of free convection due to buoyancy on forced convection heat transfer was investigated. The Reynolds numbers ranged from 120 to 1200, the Grashof numbers ranged from 0.8 × 104 to 8.7 × 104, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…This is because in the first part of the pipe, due to the effect of buoyancy the secondary flow gains momentum; but along the pipe, because of the heat balance between the fluid and wall, the buoyancy forces decrease gradually, resulting in the decrease of K. In general, the higher the Gr, the stronger the secondary flow and the sooner the maximum in K has been reached. Yousef and Tarasuk [13] in their experiment also found that there appeared a maximum value of the secondary flow near the entrance of the pipe. It can also be seen that, the smaller the inlet Reynolds number, the larger the relative magnitude of the secondary flow, and thus the larger value of K. What deserves attention is that it is for Re in = 1000 that the product f ⋅ Re has the largest value.…”
Section: Velocity and Temperature Profilesmentioning
confidence: 79%
“…This is because in the first part of the pipe, due to the effect of buoyancy the secondary flow gains momentum; but along the pipe, because of the heat balance between the fluid and wall, the buoyancy forces decrease gradually, resulting in the decrease of K. In general, the higher the Gr, the stronger the secondary flow and the sooner the maximum in K has been reached. Yousef and Tarasuk [13] in their experiment also found that there appeared a maximum value of the secondary flow near the entrance of the pipe. It can also be seen that, the smaller the inlet Reynolds number, the larger the relative magnitude of the secondary flow, and thus the larger value of K. What deserves attention is that it is for Re in = 1000 that the product f ⋅ Re has the largest value.…”
Section: Velocity and Temperature Profilesmentioning
confidence: 79%
“…Of course, in general, T(x,z * ) is not known and cannot be determined from a single interferogram. In several previous studies [60,61,62], the approach taken to overcome this difficulty has been to assume that f T is equal to the arithmetic mean fluid temperature, T . But, it is clear from eqn (50) that the effective fringe temperature f T is not the arithmetic average of T(x,z * ), integrated along the light beam.…”
Section: Beam-averaged Local Measurementsmentioning
confidence: 99%
“…Experimental results are presented by Bergles & Simonds (1971) for the case of uniform wall flux boundary, by Yousef & Tarasuk (1981) for the case of uniform wall temperature boundary and by Osborne for the case of asymmetric heating. Early work revealed that the pressure-driven axial flow was superimposed with a secondary, buoyancy-driven flow consisting of two counter-rotating vortices.…”
Section: Introductionmentioning
confidence: 99%